2018
DOI: 10.1002/lary.27204
|View full text |Cite
|
Sign up to set email alerts
|

Decision aid prototype for treatment of pediatric sleep disordered breathing: A randomized pilot study

Abstract: Objectives 1) To examine the feasibility and usability of a decision aid prototype (DA) for pediatric obstructive sleep apnea (OSA). 2) to estimate parameters for a future randomized controlled trial. Study Design Multicenter randomized pilot trial. Methods Ninety‐nine parents of children ( < 6 years of age) undergoing consultation for adenotonsillectomy for sleep‐disordered breathing were prospectively enrolled. Families were randomly assigned to receive the DA or to follow standard care procedures. All consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Discussion. The finding of no (or at most a very small) correlation between patient and clinician ratings of the patient's involvement is consistent with similar studies in pediatrics (r = .16; P = .12) and otolaryngology (r = .24; P < .01 and r = .23; P < .05) (12)(13)(14). One study included cancer survivors with many visits over an extensive period and reported a moderate correlation (r = .41; P < .01) (26).…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Discussion. The finding of no (or at most a very small) correlation between patient and clinician ratings of the patient's involvement is consistent with similar studies in pediatrics (r = .16; P = .12) and otolaryngology (r = .24; P < .01 and r = .23; P < .05) (12)(13)(14). One study included cancer survivors with many visits over an extensive period and reported a moderate correlation (r = .41; P < .01) (26).…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 88%
“…Three studies-one each in vascular surgery, anesthesiology, and dermatology-all reported differences between 7% and 39% in mean patient and physician scores but did not report correlations (9)(10)(11). One study in pediatrics and 2 in otolaryngology reported weak to moderate correlations (Spearman rho between 0.16 and 0.41) (12)(13)(14). In all 6 studies, patients rated their involvement higher than physicians.…”
Section: Introductionmentioning
confidence: 95%
“…However, studies have confirmed [3] that patients have difficulty cooperating with this training due to the influence of disease, and abnormal factors such as abnormal muscle strength and muscular tension will also lead to a poor rehabilitation effect. In addition, a study has confirmed [4] that stroke can lead to respiratory dysfunction in patients, with the clinical manifestations of weak diaphragm contraction, and decreased respiration and inspiratory muscle strength. With the development of cardiopulmonary rehabilitation, respiratory training and core muscle training play an important role in improving the respiratory function of patients with neurological diseases [5].…”
Section: Introductionmentioning
confidence: 85%
“…Several published studies relevant to otolaryngology describe patient‐oriented resources that can help educate and inform consumers about their own care 78–83 . These patient decision aids are tools that help patients navigate choices and make evidence‐based decisions when multiple options exist 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies relevant to otolaryngology describe patientoriented resources that can help educate and inform consumers about their own care. [78][79][80][81][82][83] These patient decision aids are tools that help patients navigate choices and make evidence-based decisions when multiple options exist. 84 Notably, all patient decision aids we identified in our review were published within the past 5 years, indicating their marked increase in popularity within the field.…”
Section: Other Examples Of Clinician Decision Aids Relevant To Otolar...mentioning
confidence: 99%